Collaborative Roles in Character Education: Contributions and Challenges of Principals, Teachers, and Parents in Elementary Schools - Warni Tune Sumar; Intan Abdul Razak; Fachrudin Akadji (STAI Hubbulwathan Duri, 2025)
Character education is a fundamental objective at the elementary level, with principals, teachers, and parents playing interconnected roles. This study investigates how these stakeholders collaboratively shape students' character at SDN 7 Kota Barat, Kota Gorontalo, through leadership initiatives and the integration of cultural and religious values. A qualitative research design was employed, utilizing observation, interviews, and document analysis to gather comprehensive data from school leaders, teachers, and parents. Findings reveal that principals significantly contribute to character formation by promoting discipline, modeling positive behavior, and organizing both academic and non-academic initiatives—such as congregational prayers, call-to-prayer competitions, and scouting programs—that emphasize moral and leadership development. Teachers reinforce these efforts by incorporating cultural and religious elements into instruction and encouraging collaboration, social skills, and personal responsibility. Parents support character development by instilling core moral values, practicing fairness at home, and serving as behavioral role models. However, several challenges were identified, including low student motivation, limited parental engagement, family-related issues, and inadequate school facilities. The study emphasizes that effective character development requires strong collaboration among principals, teachers, and parents. It also highlights the influence of leadership and community involvement in overcoming internal and external barriers. This research offers valuable insights for similar educational contexts, demonstrating that the synergy between leadership, instructional strategies, and parental involvement is essential in cultivating responsible, moral, and independent students.